Extratemporal Malignant Nerve Sheath Tumor of Facial Nerve with Coexistent Intratemporal Neurofibroma Mimicking Malignant Intratemporal Extension - Mitsuhiko Nakahira; Naoko Saito; Masashi Sugasawa (Case Reports in Otolaryngology)
We present an extremely unusual case of an extratemporal facial nerve malignant peripheral nerve sheath tumor (MPNST) arising from preexistent intratemporal neurofibroma, illustrating a difficulty in discriminating between perineural spread of the MPNST and the preexistent intratemporal neurofibroma on preoperative radiographic images. The most interesting point was that preoperative CT scan and MR images led to misinterpretation that MPNST extended proximally along the facial nerve canal. It is important to recognize that the intratemporal perineural spread of neurofibromas and MPNST share common imaging characteristics. This is the first report (to our knowledge) of these 2 lesions coexisting in the facial nerve, leading to misinterpretation on preoperative images.